Suicidal Intent due to Vareniclin Use Case Report - Gülmez, Özge; Akçan, Ramazan (The Bulletin of Legal Medicine, 2014)
Varenicline is the most effective pharmacological treatment currently used to for smoking cessation treatment. It is a selective partial agonist for α2-β2 nicotinic acetylcholine receptors. Although it is highly successful in smoking cessation, it is responsible for serious neuropsychiatric side effects. One of the most serious side effects in patients using Varenicline is increased suicidal intent and tendency. Here, we report a 31 years old female patient who developed suicidal intent because of Vareniclin use; therefore, attract professionals attention to the relationship between the use of Vareniclin and depression symptoms, suicide intent and suicidality. In this context, we believe that use of Vareniclin should be questioned in the patients admitted to emergency department with suicide attempts or in completed suicide cases subjected to forensic investigation.Key words: Varenicline treatment, forensic medicine, suicide.
Keywords: varenicline treatment; forensic medicine; suicide